2021
DOI: 10.1111/psyp.13921
|View full text |Cite
|
Sign up to set email alerts
|

Identifying resting state differences salient for resilience to chronic pain based on machine learning multivariate pattern analysis

Abstract: Studies have documented behavior differences between more versus less resilient adults with chronic pain (CP), but the presence and nature of underlying neurophysiological differences have received scant attention. In this study, we attempted to identify regions of interest (ROIs) in which resting state (Rs) brain activity discriminated more from less resilient CP subgroups based on multiple kernel learning (MKL). More and less resilient community-dwellers with chronic musculoskeletal pain (70 women, 39 men) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 103 publications
(114 reference statements)
2
9
0
Order By: Relevance
“…This is consistent with previous studies focused on cognitive-affective processes of pain ( Gentili et al, 2019 ; Gonzalez et al, 2019 ; You et al, 2021 ). You et al (2021) demonstrated the existence of pain-specific resilience, referring to the ability to maintain relatively stable and healthy levels of psychological functioning in face of ongoing and persistent pain ( You et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies focused on cognitive-affective processes of pain ( Gentili et al, 2019 ; Gonzalez et al, 2019 ; You et al, 2021 ). You et al (2021) demonstrated the existence of pain-specific resilience, referring to the ability to maintain relatively stable and healthy levels of psychological functioning in face of ongoing and persistent pain ( You et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“… You et al (2021) demonstrated the existence of pain-specific resilience, referring to the ability to maintain relatively stable and healthy levels of psychological functioning in face of ongoing and persistent pain ( You et al, 2021 ). Sociodemographic ( Tanner et al, 2021 ), structural and functional MRI ( Tanner et al, 2021 ; You et al, 2021 ), clinical pain symptoms, negative pain-related emotions, and PC ( Sturgeon and Zautra, 2013 ; Gonzalez et al, 2019 ) have been related to resilience and better outcomes in the presence of recurrent pain, while to our knowledge, this is the first study to explore the interaction between all these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALFF maps were used to classify chronic low back pain patients and controls with a moderate discriminate performance (accuracy rate >70%) ( 29 ). In addition, ReHo maps showed poor performance in classifying the more resilient chronic pain patients from the less resilient chronic pain patients (accuracy rate = 55%); however, the accuracy rate of combined ReHo and fractional ALFF achieved 79% ( 30 ). In the present study, the combined ALFF and ReHo showed satisfactory classification performance (accuracy rate = 93.7%) between BMP patients and HCs, which is comparable with the classification performance of FC maps.…”
Section: Discussionmentioning
confidence: 94%
“…Resilience and 'mental toughness' are similar concepts and the two terms are used interchangeably in our review. Resilience and mental toughness convey benefits across the lifespan, from childhood (11) to older adulthood (12), and it is implicated as a positive influence in outcomes as diverse as infectious disease (13), cardiometabolic health (14), cancer (15), pain (16), and mental and cognitive health (17). As mentioned above, many of these processes are also, in some way, related to sleep.…”
Section: Introductionmentioning
confidence: 99%